Synthesis and Evaluation in vitro Effects of Some Macrocyclic Thiacrown Ethers on Erythrocyte Carbonic Anhydrase I and II - Cicek, Baki; Ergun, Adem; Gencer, Nahit (Asian Journal of Chemistry, 2012)
A new series of macrocyclic thiacrown ethers (A1-6) were synthesized. These compounds were investigated as erythrocyte carbonic anhydrase I and II, which had been purified by Sepharose- 4B-L-tyrosine-sulfonamide affinity gel. These ethers showed inhibition effect for human carbonic anhydrase I and interestingly, behaved as an activator for human carbonic anhydrase II. IC50 values of the compound that caused inhibition for human carbonic anhydrase I were determined by means of activity percentage diagrams. IC50 values for macrocyclic thiacrown ethers (A1), (A2), (A3), (A4), (A5) and (A6) were determined as 1.22, 1.61, 2.11, 1.66, 0.84 and 1.45 mM respectively. Thus macrocyclic thiacrown ether (A5) was by far the most effective inhibitor.